Guest Editorial: Selected papers from RADAR 2022—International Conference on Radar Systems (Edinburgh, UK) - Clemente, Carmine; Balleri, Alessio (Institution of Engineering and Technology (IET), 2024)
It is our great pleasure to present you with this IET Radar, Sonar and Navigation special issue on the ‘Selected Papers from RADAR 2022—International Conference on Radar Systems (Edinburgh, UK)’. RADAR 2022 took place at Murrayfield Stadium, Edinburgh, on 24–27 October 2022 as a prime opportunity for radar specialists at all career stages to update and enhance their knowledge on the latest developments in advanced radar systems. As such, RADAR 2022 was attended by over 250 delegates from 22 countries who joined the conference to explore the latest technologies in radar systems.
Special Issue: Selected Papers from RADAR 2022 ‐ International Conference on Radar Systems (Edinburgh, UK)